Analisis Tingkat Pemahaman Siswa pada Materi Perubahan dan Pelestarian Lingkungan di Kelas X SMA Negeri 1 Tilango - Fadila Bau; Ani M. Hasan; Chairunnisah J. Lamangantjo (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to analyze the level of student understanding of environmental change and conservation in grade X of SMA Negeri 1 Tilango. The study used a descriptive quantitative approach, involving 25 grade X3 students. The method used was a multiple-choice test based on seven indicators of understanding: identifying, explaining, interpreting, classifying, comparing, summarizing, and understanding. The results showed that all indicators improved from the pretest, which was generally in the low category, to the posttest, which reached an average of 77.81%, categorized as high. This improvement reflects that the applied learning process was able to improve students' conceptual mastery of environmental change and conservation, while simultaneously strengthening their analytical thinking skills. A comparison of pretest and posttest scores indicates that the instrument used was effective in measuring students' conceptual understanding and that the applied learning positively influenced learning outcomes.